EMBODIED EXPERIENCES OF DRAWING: A PHENOMENOLOGICAL INQUIRY INTO STRESS AND EVERYDAY LIFE IN ART EDUCATION - Ankyiah, Francis (ISI Press Institut Seni Indonesia Surakarta, 2023)
Drawing's impact on students' stress levels and coping with daily life is underexplored. This study used a phenomenological approach to understand how undergraduates experience drawing in art studio courses. Five art students were interviewed during regular assignments, and Moustakas' method was used to analyse the data. Three themes emerged: drawing as an